Minimizing ED Waiting Times and Improving Patient Flow and Experience of Care - Sayah, Assaad; Rogers, Loni; Devarajan, Karthik; Kingsley-Rocker, Lisa; Lobon, Luis F. (Emergency Medicine International, 2014)
We conducted a pre- and postintervention analysis to assess the impact of a process improvement project at the Cambridge Hospital ED. Through a comprehensive and collaborative process, we reengineered the emergency patient experience from arrival to departure. The ED operational changes have had a significant positive impact on all measured metrics. Ambulance diversion decreased from a mean of 148 hours per quarter before changes in July 2006 to 0 hours since April 2007. ED total length of stay decreased from a mean of 204 minutes before the changes to 132 minutes. Press Ganey patient satisfaction scores rose from the 12th percentile to the 59th percentile. ED patient volume grew by 11%, from a mean of 7,221 patients per quarter to 8,044 patients per quarter. Compliance with ED specific quality core measures improved from a mean of 71% to 97%. The mean rate of ED patients that left without being seen (LWBS) dropped from 4.1% to 0.9%. Improving ED operational efficiency allowed us to accommodate increasing volume while improving the quality of care and satisfaction of the ED patients with minimal additional resources, space, or staffing.